Effects of cyclic compressive loading and self healing on the mechanical and permeability properties of concrete - Akakın, Tümer. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Concrete, when subjected to repeated loads, may exhibit excessive cracking and may eventually fail after a sufficient number of load repetitions, even if the maximum stress applied is less than the static strength of a similar specimen. In this study, up to 100 cycles of compression loading is applied to 100x200 mm concrete cylinders with an average 28 day compressive strength of 38 MPa. The stress ratios (applied stress/ultimate stress) were 0.9, 0.8 and 0.6. Stress-strain behavior and modulus of elasticity were determined during cyclic loading, and ultrasonic pulse velocity and splitting tensile strength tests were carried out on cyclically loaded specimens. For the stress ratio 0.9fmax the modulus of elasticity, splitting tensile strength, ultrasonic pulse velocity and compressive strength decreased as 47, 30, 8 and 6 percentages respectively after 100 cycles of loading. After water curing applied on the cyclic loaded specimens, 62, 5, 22, and 8 percentages increases were obtained for the modulus of elasticity, compressive strength, tensile splitting strength and ultrasonic pulse velocity, respectively, due to self healing. The permeability properties were investigated through rapid chloride permeability, water absorption, sulphate attack and mercury intrusion tests. Mercury intrusion tests revealed that total pore volume and total pore area were higher for cyclically loaded specimen compared with the unloaded specimen. The crack sizes for higher loading ratios were found larger and with self healing effect the cracks could get closer. The post peak responses were investigated and the change in behavior was found to change with cyclic loading.
Keywords: Concrete -- Mechanical properties.; Concrete -- Permeability.